PENERAPAN MODEL BELAJAR COOPERATIVE SNOWBALL THROWING DALAM PEMBELAJARAN TEMATIK KELAS 1 - Nur Laely (Educreative : Jurnal Pendidikan Kreativitas Anak, 2020)
Thepurpose of this study was to determine the Application of Cooperative Snowball Throwing Learning Model in Thematic Learning Class 1 at MIN 3 Banyumas Academic Year 2019-2020. The type of research data used in this study is a quantitative-qualitative approach (mexing method). The subjects of this study were class I MIN 3 Banyumas Lessons in 2019-2020 totaling 33 students. The techniques used in data collection are interview, documentation, observation and test techniques. The results showed that the application of the Cooperative Snowball Throwing Learning Model could improve the thematic learning outcomes at MIN 3 Banyumas in 2019-2020. This can be proven by the learning outcomes for each cycle. In cycle I, the average score of student learning test results was 67.73, the lowest score was 45.00 and the highest score was 90.00. This is known by comparing the pre-cycle value with the value of Cycle I, the test results where the value of Cycle I is greater than the pre-cycle of the average value, namely: 67.73> 55.30. Whereas in the second cycle, the average test score was 75.91, while the lowest score was 55.00 and the highest score was 95.00. this can be known by comparing the value of the first cycle with the second cycle, the test results in which the value of the second cycle test is greater than the first cycle with an average value of 75.91> 67.73. And in the third cycle it can be seen that the average value of the test results is 83.79, while the lowest value is 65.00 and the highest value is 100.00.